Palm oil fuel ash as potential green micro-filler in polymer concrete - Khalid, N.; Hussin, M.; Mirza, J.; Ariffin, N.; Ismail, Mohamed; Lee, H.; Mohamed, A.; Jaya, R. (Elsevier BV, 2016)
Being a plant with open cellulose structure, such potential has gone untapped due to its tendency to take up excessive resin during the mixing process. Hence, this paper presents the potential of utilizing an agricultural waste; palm oil fuel ash (POFA) as micro-filler in polymer concrete (PC). Two types of POFA fillers - ground (GPOFA) as fine filler and unground (UPOFA) as coarse filler were investigated in different contents. For comparison purpose, GPOFA was paired with calcium carbonate while UPOFA was with silica sand. Filler characteristics were studied through microstructural examination, particle size distribution, nitrogen absorption test, morphology image, and thermal analyses. Forty polymer blended and polymer concrete mixes were prepared for flowability and compression tests, respectively. Then, miniature crushed specimens were tested using Mercury Intrusion Porosimetry (MIP) and Field Emission Scanning Electron Microscopy (FESEM) to investigate porosity and morphology of PC, respectively. Results showed that POFA had their physical features changed significantly after surface modifications. The ground POFA gives superior filling ability and high PC compressive strength. Additionally, good dispersion characteristic of POFA could reduce porosity in PC as well. It can be concluded that POFA can be potentially utilized as effective PC filler after being subjected to some physical modifications and mixing it with appropriate mix design.